Evolving Trends of Gastrostomy Insertion Within a Pediatric Population. Issue 5 (November 2018) - Glasson, Emma J.; Wong, Kingsley; Leonard, Helen; Forbes, David; Ravikumara, Madhur; Mews, Catherine; Jacoby, Peter; Bourke, Jenny; Trollor, Julian; Srasuebkul, Preeyaporn; Wilson, Andrew; Nagarajan, Lakshmi; et al.
ABSTRACT: Objective: Gastrostomy insertion in pediatrics is usually used in children with complex needs and severe disability. The accessibility and acceptance of the procedure is increasing but population-based occurrence data are lacking and there is limited understanding of its use in clinical subgroups. Methods: This birth cohort study investigated the trends in first gastrostomy insertion among a pediatric population born between 1983 and 2009 in Western Australia using linked administrative and health data collected over a 32-year period (1983–2014). Indications were identified using diagnosis codes from linked hospitalization data and grouped according to a refined classification system. Age and birth cohort patterns of first gastrostomy use, over calendar year and age respectively, were described. Results: Of the 690, 688 children born between 1983 and 2009, 466 underwent a gastrostomy insertion. Overall, the prevalence was approximately 7 cases per 10, 000 births. New gastrostomy insertions were increasingly performed in children during the preschool years over calendar years and in successive birth cohorts. Children with a neurological disorder constituted the largest group receiving gastrostomy (n = 372; 79.8) including 325 (87.4%) with comorbid intellectual disability. Conclusions: New gastrostomy insertion among children who require long-term enteral feeding support increased over the study period. The procedure is most often performed in the context of severe neurological disability, including intellectual disability, and offers families potential for long-term home-based management of feeding difficulties.